Artocarpus heterophyllus seeds powder in scrub formulation / Norshafika Mustofa - Mustofa, Norshafika (2015)
In scrub formulation, the stability of the formulation along with rheological and spreadability properties are the most important aspects to be considered during the production process. In this research, the effects of incorporation of Artocarpus heterophyllus (jackfruit) seeds powder on the stability, rheological and spreadability behavior of scrub formulation were evaluated. In general, the addition of jackfruit seeds powder increased the viscoelastic properties of the scrub formulation. Incorporation of jackfruit seeds powder led to better stability of the scrub formulation. Texture analysis results of scrub formulation incorporated with jackfruit seeds powder were shown to have better spreadability property.